“Out of the blue”, a new species of the monotypic genus Kinku Simon, 1889 (Araneae, Telemidae) from Ecuador - Dupérré, Nadine; Tapia, Elicio (Zootaxa, 2025)
The second species of the enigmatitc genus Kinku Dupérré & Tapia, 2015 is described from Ecuador. The new species Kinku maicu sp. nov. (♂♀) possesses the same typical blue coloured abdomen, as well as the presence in males of an abdominal stridulatory organ as found in the type species. SEMs photos of the male stridulatory organ, female spinnerets and, internal genitalia are presented for the first time.